2019
DOI: 10.1002/pssr.201900397
|View full text |Cite
|
Sign up to set email alerts
|

Transient Resistive Switching for Nonvolatile Memory Based on Water‐Soluble Cs4PbBr6 Perovskite Films

Abstract: All‐inorganic halide perovskite Cs4PbBr6 thin films are synthesized at low temperature through a facile chemical deposition method. The deposited films are implemented as a dielectric and dissolvable layer with the Au/Cs4PbBr6/PEDOT:PSS/ITO configuration for transient memory electronic devices. The bipolar resistive switching phenomena, good switching cycling (endurance), and long data retention (104 s) are demonstrated on as‐grown nonvolatile memory device to evaluate its high stability, reliability, and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Furthermore, great efforts have been devoted to exploring new inorganic materials such as perovskite for environmental applications, especially halide perovskite [33,[76][77][78][79][80][81]. Some researches indicate that halide perovskite materials can also be utilized for various applications in terms of environmental protection, for instance, environmental-friendly sensors, disposable consumer devices, and green electronics [77,[80][81][82]. The products we use today are more environmental-friendly and efficient, while the method of obtaining energy is definitely less harmful.…”
Section: Inorganic Thin-film Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, great efforts have been devoted to exploring new inorganic materials such as perovskite for environmental applications, especially halide perovskite [33,[76][77][78][79][80][81]. Some researches indicate that halide perovskite materials can also be utilized for various applications in terms of environmental protection, for instance, environmental-friendly sensors, disposable consumer devices, and green electronics [77,[80][81][82]. The products we use today are more environmental-friendly and efficient, while the method of obtaining energy is definitely less harmful.…”
Section: Inorganic Thin-film Materialsmentioning
confidence: 99%
“…Perovskite-based thin films were used as a sensing material to develop high-performance gas sensors for the detection of acetone or nitrogen dioxide (NO 2 ) at room temperature. To date, some efforts have been carried out using perovskite materials as a promising candidate for transient and disposable devices [80,81,116,117]. In 2018, Li et al for the first time proposed that the transient resistive-switching electronic device with the perovskite CsPbBr 3 thin-films acting as resistive-switching functional layer [80].…”
Section: Halide Perovskite Thin-filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, OIHPs exhibit satisfactory transient property for emerging transient devices with rapid dissolution in deionized water. [ 39,40 ] Herein, exploring OIHPs in transient memory device via simple process in ambient atmosphere is rather significant in the development of perovskite memory.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, oxygen annealing is one of most effective approach in reducing the strength of oxygen vacancies, which consequently enhances the switching parameters. Chen et al [16] [20] introduced rapid thermal annealing in atomic layer deposited ZrO 2 thin film, and found improvement in endurance, uniformity and ON/OFF ratio, respectively. Yang et al [21] reported that memory devices after rapid thermal annealing demonstrated remarkable improvement in switching characteristics as compared to as-fabricated devices.…”
Section: Introductionmentioning
confidence: 99%